RETHINKING THE USE OF ARCHITECTURAL HERITAGE ELEMENTS AS A TOOL TO AVOID THE HEALTH RISK OF VITAMIN D DEFICIENCY: AN EXPERIENCE FROM MADINAH, SAUDI ARABIA - Ashour, Randah (JIAA: Journal of Islamic Art and Architecture, 2024)
This research aims to assess the public’s awareness, knowledge and attitude toward vitamin D and sun exposure in Madinah, as well as to evaluate people’s satisfaction with the different techniques used to maintain daylight at their homes. A cross-sectional study utilizing an online survey was conducted. Data analysis was performed using SPSS software. A total of 925 participants took part in this study. The majority of participants were 30-49 years old (55%), Saudis (69.2%), house owners (53%), and living in flat property (54.8%). 92% believed that vitamin D is important for health and 55.6% reported that vitamin D source was the sun. Unfortunately, 17.2% and 10.2% recognized the best time of sun exposure and the appropriate duration of sun exposure for adequate vitamin D, respectively. 73.6% suffered from the symptoms of vitamin D deficiency. Hot weather (59.3%), conservative dressing of Saudi women (26%) and increased urbanization and increased indoor lifestyle (10.3%) were key barriers to sunlight exposure in Madinah. 75.4% satisfied with the level of daylight provided by Rowshan. However, due to its high cost and difficulty to clean, most of the people reluctance to use Rowshan. This study found inadequate knowledge, and poor practice about vitamin D and sun exposure.